2020
DOI: 10.6115/fer.2020.037
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Model of the Intent of Work-Family Multiple-Role Planning among Female University Students: Integration of Social Cognitive Career Theory and Theory of Planned Behavior

Abstract: This study presents work-family multiple-role planning by female university students as a new approach to work-life balance. Accordingly, this study examines university years as a key time frame during which students establish their career paths. This study integrates the social cognitive career theory and the planned behavior theory to design and evaluate a model that explains the work-family multiple-role planning process; in addition, it develops an optimal model to predict the intentions of female universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 37 publications
0
0
0
Order By: Relevance
“…Another study identified gender differences when predicting safer sexual behav-iors among university students in Korea using the TPB model. Communication was found to have a direct effect on female students regarding safer sexual behaviors, while it showed no significant effect on male students [23].…”
Section: Summary Statementmentioning
confidence: 79%
“…Another study identified gender differences when predicting safer sexual behav-iors among university students in Korea using the TPB model. Communication was found to have a direct effect on female students regarding safer sexual behaviors, while it showed no significant effect on male students [23].…”
Section: Summary Statementmentioning
confidence: 79%